2013
DOI: 10.1161/strokeaha.111.000204
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Quality Initiative to Maximize Dysphagia Screening Reduces Hospital-Acquired Pneumonia Prevalence in Patients With Stroke

Abstract: Background and Purpose-Dysphagia can lead to pneumonia and subsequent death after acute stroke. However, no prospective study has demonstrated reduced pneumonia prevalence after implementation of a dysphagia screen. Methods-We performed a single-center prospective interrupted time series trial of a quality initiative to improve dysphagia screening. Subjects included all patients with ischemic or hemorrhagic stroke admitted to our institution over 42 months with a 31-month (n=1686) preintervention and an 11-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 28 publications
3
76
1
6
Order By: Relevance
“…18 The rate of PSP diagnosis is dependent on the diagnostic criteria used. 19 Physicians are influenced by stroke severity and poor expectation of outcome in diagnosing pneumonia 20 ; it is likely that the presence of NGT further increases this clinical bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The rate of PSP diagnosis is dependent on the diagnostic criteria used. 19 Physicians are influenced by stroke severity and poor expectation of outcome in diagnosing pneumonia 20 ; it is likely that the presence of NGT further increases this clinical bias.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that preventive antibiotics do not add to existing measures to prevent aspiration on specialist stroke units. 18 Antibiotic prophylaxis is based on the assumption of an infective pathogenesis for PSP; it has been suggested that aspiration of gastric/ esophageal contents may result in pneumonitis of complex bacterial, chemical, and immunologic origins, 23 for which novel strategies need to be investigated. 24 A limitation of the study was that the data were derived from a randomized controlled trial and a prospective cohort data structure was assumed.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that a failed swallow test independently predicted pneumonia 15 and that introducing a formal swallow test more than halved pneumonia rate. 2,[17][18][19] Thus, identifying patients at nutritional risk and patients with dysphagia as soon as possible after admission helps to ensure optimal nutritional management in all patients with stroke and to reduce the risk of aspiration in patients with dysphagia. Application of formal screening tests is likely to reduce complications, prolonged hospital stay, poor functional outcomes, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…3 Given the clinical impact, efforts to reduce this complication are important. Pneumonia prediction models have been developed for clinical use [4][5][6] and various interventions to prevent pneumonia have been evaluated, [7][8][9][10][11] but more research in these areas is needed. The ability to synthesize the literature is difficult because of the variability in the frequencies of pneumonia reported across studies, which is further complicated by differences in definitions of pneumonia used in clinical studies.…”
mentioning
confidence: 99%